PENEGAKAN HUKUM TERHADAP PERDAGANGAN PRODUK BARANG ILEGAL BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Winda Yunita; Riza Yudha Patria (Fakultas Hukum Universitas Tulang Bawang, 2022)
Article 62 of the Criminal Code states that trading in illegal goods is a crime, and this is enforced in conjunction with other laws that protect consumers. How is law enforcement against trade in illegal goods products based on Law Number 8 of 1999 concerning Consumer Protection. What are the disincentives for law enforcement efforts against the crime of counterfeiting illegal products? This study uses a legal-regulatory approach. Based on the results of the study and discussion, it shows that law enforcement in relation to trade in illegal commercial products based on Law Number 8 of 1999